Separation and Determination of Some Organic Acids in Dry Calyces of Iraqi Hibiscus Sabdariffa Linn (Baghdad Science Journal, 2015)
A new reversed phase- high performance liquid chromatographic (RP-HPLC) method with Ultraviolet-Visible spectrophotometry has been optimized and validated for the simultaneous extraction and determination of organic acids present in Iraqi calyces of Hibiscus Sabdraffia Linn. The method is based on using ultrasonic bath for extracting organic acids. Limit of detection in µg/ml of Formic acid, Acetic acid, Oxalic acid, Citric acid, Succinic acid, Tartaric acid, and Malic acid 126.8498×10-6, 113.6005×10-6, 97.0513×10-6, 49.7925×10-6, 84.0753×10-6, 92.6551×10-6, and 106.1633×10-6 ,respectively. The concentration of organic acids found in dry spacemen of calyces of Iraqi Hibiscus Sabdraffia Linn. under study: Formic acid, Acetic acid, Oxalic acid, Citric acid, Succinic acid, Tartaric acid, and Malic acid are 114.896 µg/g, 64.722 µg/g, 342.508 µg/g, 126.902 µg/g, 449.91 µg/g, 268.52 µg/g, and 254.07 µg/g respectively.